Influence of forest canopy structure on temperature buffering in young planted forests with varied tree species compositions revealed by terrestrial laser scanning - Wang, Mengxi; Blondeel, Haben; Gillerot, Loïc; Verbeeck, Hans; Van Coillie, Frieke; Meunier, Félicien; Zhang, Shengmin; De Frenne, Pieter; Verheyen, Kris; Calders, Kim (Agricultural and forest meteorology, 2025)
•Forest canopy impacts were analyzed using TLS and microclimate data from 2021.•Below-canopy air temperature buffering was stronger in summer than winter.•Pine proportion was a key driver of temperature buffering.•Canopy structure had limited explanatory power but potential influence.•SLA, an indirect proxy of transpiration potential, showed strong summer cooling. Forest structure mediates below-canopy temperatures, creating unique microclimates for forest organisms. However, the understanding of how intricate forest canopy structure affect below-canopy air temperatures remains incomplete, especially in early-stage planted forests. Additionally, conventional forest structure metrics lack detailed structural information. We used 156 Terrestrial Laser Scanning single scans from 39 plots in a tree diversity experiment located at Zedelgem, Belgium, to explore how tree diversity and canopy structure affect below-canopy temperature. Five site-adapted species were planted, with plots varying in tree species richness from monocultures to four-species mixtures across twenty composition levels. Vertical plant profiles were derived from four scan locations per plot, allowing for the calculation of four variables to describe various aspects of forest canopy structure: foliage height diversity, total plant area index, canopy height, and canopy openness. Our findings showed that below-canopy temperature buffering was stronger in summer than in winter, with pine proportion dominating the buffering effect. Although canopy structure explained a small portion of the variance, it showed notable buffering potential, with summer cooling associated with low canopy openness and winter warming linked to high foliage height diversity and low canopy openness. Moreover, the community weighted mean specific leaf area, as an indirect proxy for transpiration potential, demonstrated strong summer cooling. Our findings suggest that local forest management strategies focused on temperature buffering should consider increasing pine proportions, as they enhance the buffering capacity in early forest development. As the forest matures, the advantages of a more diverse and denser canopy may become more apparent.